Species-specific inhibition of porphobilinogen synthase by 4-oxosebacic acid - Jaffe, Eileen; Kervinen, Jukka; Martins, Jacob; Stauffer, Frédéric; Neier, Reinhard; Wlodawer, Alexander; Zdanov, Alexander (My University, 2002)
Porphobilinogen synthase (PBGS) catalyzes the condensation of two molecules of 5-aminolevulinic acid (ALA), an essential step in tetrapyrrole biosynthesis. 4-Oxosebacic acid (4-OSA) and 4,7-dioxosebacic acid (4,7-DOSA) are bisubstrate reaction intermediate analogs for PBGS. We show that 4-OSA is an active site-directed irreversible inhibitor for Escherichia coli PBGS, whereas human, pea, Pseudomonas aeruginosa, and Bradyrhizobium japonicum PBGS are insensitive to inhibition by 4-OSA. Some variants of human PBGS (engineered to resemble E. coli PBGS) have increased sensitivity to inactivation by 4-OSA, suggesting a structural basis for the specificity. The specificity of 4-OSA as a PBGS inhibitor is significantly narrower than that of 4,7-DOSA. Comparison of the crystal structures for E. coli PBGS inactivated by 4-OSA versus 4,7-DOSA shows significant variation in the half of the inhibitor that mimics the second substrate molecule (A-side ALA). Compensatory changes occur in the structure of the active site lid, which suggests that similar changes normally occur to accommodate numerous hybridization changes that must occur at C3 of A-side ALA during the PBGS-catalyzed reaction. A comparison of these with other PBGS structures identifies highly conserved active site water molecules, which are isolated from bulk solvent and implicated as proton acceptors in the PBGS-catalyzed reaction.
Keywords: X-RAY STRUCTURE; ESCHERICHIA-COLI; PSEUDOMONAS-AERUGINOSA; ARTIFICIAL; GENE; DEHYDRATASE; RESOLUTION; MECHANISM; MG(II); IONS